TP53 Germline Mutations in Adult Patients with Adrenocortical Carcinoma - Herrmann, Leonie J. M.; Heinze, Britta; Fassnacht, Martin; Willenberg, Holger S.; Quinkler, Marcus; Reisch, Nicole; Zink, Martina; Allolio, Bruno; Hahner, Stefanie (The journal of clinical endocrinology and metabolism, 2012)
Context:Li-Fraumeni syndrome (LFS) is a cancer predisposition syndrome associated with germline mutations in TP53. According to the Chompret criteria for LFS, any patient with adrenocortical cancer (ACC), irrespective of age and family history, is at high risk for a TP53 germline mutation. However, whereas such mutations have been detected with high frequency in childhood ACC, a large cohort of adult patients with ACC has never been investigated for TP53 germline mutations.Objective:The aim of the study was to evaluate the prevalence of TP53 germline mutations in adult patients with ACC.Subjects and Methods:In 103 adult Caucasian patients with ACC, TP53 germline mutation analysis was performed. In patients with a TP53 germline mutation, tumor tissue was analyzed for loss of heterozygosity of TP53 and p53 immunohistochemistry. Family history and clinical course were also evaluated.Results:In four patients, a total of five TP53 germline mutations were found. Two mutations occurred in exon 10 (R337H and I332M, respectively), outside the hot spot region. Here, three mutations are described for the first time in ACC, and one, which occurred combined with a second mutation (R202C) on the same allele, has never been reported before in the context of LFS. This combined mutation was associated with a remarkable family history of ACC also affecting the mother and uncle of the index patient. In the 23 patients with ACC below the age of 40 yr, 13% (95% confidence interval, 3.7–32.9%) carried a TP53 germline mutation, whereas such mutations were rare in older patients with ACC.Conclusion:Our findings indicate a need to revise the Chompret criteria. However, in younger adults (<40 yr old) with ACC, screening for TP53 germline mutations may be justified.